Interpreting qualitative data - Silverman, David (SAGE, 2014)
In this fifth edition of his field-defining text, David Silverman, a true guru of qualitative research, walks the reader through the basics of gathering and analyzing qualitative data. The book offers beginners unrivalled hands-on guidance to help them get the best out of a research methods course or research project.